Analisis Kelayakan Penggunaan Artificial Intelligence dalam Pembelajaran Menggambar Bangunan Sipil di Teknik Sipil UNSIKA - Masyita, Nurani (CV. Green Publisher Indonesia, 2025)
The rapid development of technology in higher education encourages the integration of Artificial Intelligence (AI) into the learning process, including in the Civil Building Drawing course. Students of the Civil Engineering Study Program at UNSIKA often face difficulties in understanding technical drawings due to their educational background and the conventional methods used in teaching. This study aims to evaluate the feasibility and readiness of implementing AI technology in the drawing course using the CIPP (Context, Input, Process, Product) evaluation model. This is a descriptive-evaluative research involving 46 students who have completed the subject. Data were collected through a Likert-scale questionnaire and analyzed descriptively. The results indicate that all four evaluation components are in the “Good” category, with the highest score in the process component and the lowest in the product component. These findings suggest that while students generally accept AI-assisted learning processes, there is still uncertainty about its tangible impact on learning outcomes. It is concluded that AI holds strong potential to enhance the quality of technical drawing education, provided there are improvements in planning, student engagement, and structured learning outcome evaluation.